Մասնագիտական շարունակական զարգացման կազմակերպումը Հայաստանի ազգային գրադարանի օրինակով - Թամազյան, Տաթևիկ (Հայաստանի ազգային գրադարան / National Library of Armenia, 2023)
Continuous professional development and lifelong learning should be an integral part of every li-brarian’s work. Over the years, librarian’s participation in various workshops, trainings, direct or remote seminars is very important for their professional growth, to avoid stagnation, to acquire new skills and knowledge, and thus to face the challenges that arise with changes in work over time. The article presents the activities of the National Library of Armenia aimed at the professional development of librarians of both national and other libraries of Armenia, with the aim of creating pre-requisites for professional development and new achievements in the workplace.
Բանբեր Հայաստանի գրադարանների ։ Գիտամեթոդական հանդես ։ Հատուկ թողարկում / Գլխավոր խմբագիր` Աննա Չուլյան ; Պատասխանատու խմբագիր՝ Հայկանուշ Ղազարյան ․- Երևան ։ «Գիրք» հրատարակչություն , 2023 ․- էջ 104 - 107
Keywords: Գրադարանագիտություն, մատենագիտություն և արխիվավարություն